Voting on the Budget Deficit - Tabellini, Guido; Alesina, Alberto (American Economic Review, 1990)
This paper analyzes a model in which a group of rational individuals votes over the composition and time profile of public spending. All voters agree that a balanced budget is ex ante optimal. However, if there is disagreement between current and future majorities, a balanced budget is not a political equilibrium under majority rule. Under certain conditions a majority of the voters favors a budget deficit, and the equilibrium deficit is larger the greater is the polarization among voters.